Clusia Holy Grail and enigma - Lüttge, Ulrich (Journal of experimental botany, 2008)
Clusia is the only genus with bona fide dicotyledonous trees performing Crassulacean acid metabolism (CAM). Clusia minor L. is extraordinarily flexible, being C(3)/CAM intermediate and expressing the photosynthetic modes C(3), CAM, CAM-cycling, and CAM-idling. C(3) photosynthesis and CAM can be observed simultaneously in two opposite leaves on a node and possibly even within the same leaf in the interveinal lamina and the major vein tissue, respectively. The relative activity of photosystem II (PhiPSII) indicating photosynthetic energy use, is larger under photorespiratory than under non-photorespiratory conditions due to the particular energy demand of photorespiration. The heterogeneity of PhiPSII over the leaves as visualized by chlorophyll fluorescence imaging in the C(3) mode is larger under non-photorespiratory conditions than under photorespiratory conditions. These observations indicate that photorespiration, presumably by its particular energy demand, synchronizes photosynthetic activity over the leaves. In the CAM mode, the heterogeneity of PhiPSII is more dependent on the transitions between CAM phases. Free-running circadian oscillations of photosynthesis are strongly dampened in both the C(3) and the CAM mode. Photorespiration is under circadian clock control in both the C(3) and the CAM mode. PhiPSII and the heterogeneity of PhiPSII oscillate in phase with CO(2) uptake and photorespiration only under non-photorespiratory conditions. Under photorespiratory conditions, PhiPSII does not oscillate and there is no heterogeneity, again indicating the stabilizing function of photorespiration. Plants acclimatized to perform CAM switch to C(3) photosynthesis during free-running oscillations while subjected to constant illumination